Advanced Technologies from and Through a Prototype Radio Lesson with Budding Journalists: The Views and Attitudes of Xers, Millennials, and Zoomers - Constantinos Nicolaou (Applied Sciences)
In this research article, budding journalists’ views and attitudes toward a prototype radio lesson that was designed and implemented utilizing advanced technologies are explored. These budding journalists hail from Greece, were studying in higher education or adult education at the time of the survey, and belong to one of the three youngest generational cohorts within adults (i.e., 18 years old and older); Generation X where their members are now known as Xers, Generation Y where their members are already known as Millennials, and Generation Z where their members are also known as Zoomers—XYZ Generations. The survey’s research data were collected after six interactive teachings from and through advanced technologies, via a specially designed written questionnaire, as case study experiments that applied qualitative action research with quasi-experiments. Analysis, descriptive, and inductive statistics were then applied to them from and through Internet applications and services. This is essentially empirical qualitative research that incorporates the approach of the quantitative analysis process. The resulting survey findings and results mainly contribute to the quality of higher education and adult education, especially in the field of media studies. Likewise, they align with or confirm previous contemporary empirical studies and research papers on the genealogical characteristics, habits, and ethos of the XYZ Generations, and particularly regarding the similarities among Xers and Zoomers, as well as that Generation Z can also be characterized as a “Sound Generation”. An important conclusion of this research article is that the success of a lesson or even a lecture seems to depend (a) on the good design and/or development of the lesson plan itself, as well as (b) on the communication classroom where the educational praxis takes place. Finally, these survey findings and results are also considered encouraging and could be utilized (a) for any audiovisual-supported teaching–learning procedure for adult learners; (b) across various educational levels and disciplines; or even (c) for members other generational cohorts.